How to evaluate for immunodeficiency in patients with autoimmune cytopenias: laboratory evaluation for the diagnosis of inborn errors of immunity associated with immune dysregulation - Abraham, Roshini S. (Hematology Am Soc Hematol Educ Program, 2020)
The identification of genetic disorders associated with dysregulated immunity has upended the notion that germline pathogenic variants in immune genes universally result in susceptibility to infection. Immune dysregulation (autoimmunity, autoinflammation, lymphoproliferation, and malignancy) and immunodeficiency (susceptibility to infection) represent 2 sides of the same coin and are not mutually exclusive. Also, although autoimmunity implies dysregulation within the adaptive immune system and autoinflammation indicates disordered innate immunity, these lines may be blurred, depending on the genetic defect and diversity in clinical and immunological phenotypes. Patients with immune dysregulatory disorders may present to a variety of clinical specialties, depending on the dominant clinical features. Therefore, awareness of these disorders, which may manifest at any age, is essential to avoid a protracted diagnostic evaluation and associated complications. Availability of and access to expanded immunological testing has altered the diagnostic landscape for immunological diseases. Nonetheless, there are constraints in using these resources due to a lack of awareness, challenges in systematic and logical evaluation, interpretation of results, and using results to justify additional advanced testing, when needed. The ability to molecularly characterize immune defects and develop “bespoke” therapy and management mandates a new paradigm for diagnostic evaluation of these patients. The immunological tests run the gamut from triage to confirmation and can be used for both diagnosis and refinement of treatment or management strategies. However, the complexity of testing and interpretation of results often necessitates dialogue between laboratory immunologists and specialty physicians to ensure timely and appropriate use of testing and delivery of care.